Comparative Study of Laparoscopic Appendectomies With Application of Different Techniques for Closure of the Appendicular Mesoappendix and Stump (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: Laparoscopic appendectomy(LA) has gained a wide safe acceptance and effective method for treatment of acute appendicitis and can be considered as a gold standard. The aim of the study was to evaluate the results of LA performed with the use of different techniques. Method: Prospective randomized comparative study was carried out in a Babylon General Teaching Hospital. Patients diagnosed with acute appendicitis between December 2011 and December 2015 and agreed to do LA were included in this study. In Group A , the mesoappendix and the base of appendix is ligated using titanium clips while in group B ,the mesoappendix was cut with the application of monopolar diathermy very near to the appendix wall and the base of appendix is ligated using vicryle endoloop. In. Primary outcomes were assessed which include mortality ,intra and post-operative complication rate, reinterventions, and converted laparoscopic appendectomies to open .Secondary outcomes were time of hospitalization, duration of operation, wound infection and intra-abdominal abscesses formation rate, hospital charges. Result: A total of 284patients underwent LA. 146 (51.4%) of them ,LA were done by clipping of mesoappendix and base of appendix by titanium clips, while the other 138 (48.6%) of patients LA were done by using monapolar diathermy to the mesoappendix and base of appendix secured by vicryle endoloop. The overall mean age of all patients with appendectomy was (26.42±11.05) years old and (38.7%) of patients were aged between 20-30 years. (52.5%) of patients were males. The overall mean weight, height and BMI for patients with appendectomy were (74.29±12.14) kg, (1.68±0.09) m and (26.68±8.84) kg/m2, respectively. (45.4%) of patients were overweight. The overall mean duration of operation was (31.01±12.48) min and (68.7%) of patients spent less than 30 min operative time, meanwhile, the mean of hospitalization after operation was (22.11± 17.96) hours and (71.8%) of patients stayed less than 20 hours in hospital. Only (8.5%) of patients had complicated appendicitis and complication post-operation, while, (4.9%) of patients had complicated appendectomy. (45.1%) of operations’ cost were 450 US $. There were significant associations between type of appendectomy with duration, complicated operation and price of operation. Conclusion: Laparoscopic appendectomies can be considered a safe treatment of complicated and non complicated appendicitis. Application of monopolar diathermy very near to the wall of appendix to cauterize the small vessels of mesoappendix is useful and safe and considered costly effective and less complication rate than application of Titanium clips.